First Apocarotenoids Profiling of Four Microalgae Strains - Mariosimone Zoccali; Daniele Giuffrida; Fabio Salafia; Carmen Socaciu; Kari Skjånes; Paola Dugo; Luigi Mondello (MDPI AG, 2019)
Both enzymatic or oxidative carotenoids cleavages can often occur in nature and produce a wide range of bioactive apocarotenoids. Considering that no detailed information is available in the literature regarding the occurrence of apocarotenoids in microalgae species, the aim of this study was to study the extraction and characterization of apocarotenoids in four different microalgae strains: Chlamydomonas sp. CCMP 2294, Tetraselmis chuii SAG 8-6, Nannochloropsis gaditana CCMP 526, and Chlorella sorokiniana NIVA-CHL 176. This was done for the first time using an online method coupling supercritical fluid extraction and supercritical fluid chromatography tandem mass spectrometry. A total of 29 different apocarotenoids, including various apocarotenoid fatty acid esters, were detected: apo-12'-zeaxanthinal, β-apo-12'-carotenal, apo-12-luteinal, and apo-12'-violaxanthal. These were detected in all the investigated strains together with the two apocarotenoid esters, apo-10'-zeaxanthinal-C4:0 and apo-8'-zeaxanthinal-C8:0. The overall extraction and detection time for the apocarotenoids was less than 10 min, including apocarotenoids esters, with an overall analysis time of less than 20 min. Moreover, preliminary quantitative data showed that the β-apo-8'-carotenal content was around 0.8% and 2.4% of the parent carotenoid, in the C. sorokiniana and T. chuii strains, respectively. This methodology could be applied as a selective and efficient method for the apocarotenoids detection.